“Now pay them back in their turn, without yielding to present weakness”: death and politics in the Thucydides’ ‘History of the Peloponnesian War’ - Machado Gomes, Caio César (Romanitas - Revista de Estudos Grecolatinos, 2023)
I explore how Thucydides, in his History of the Peloponnesian War, dealt with some issues related to the political calculation of death as carried out by the Athenians, with emphasis on the narrative of the armed conflict between Athens and Mytilene, which occurred between 428 and 427 BCE (Thuc., III, 1-19; 25-50). At this point, disregarding for the rules that shaped the Hellenic “code of conduct” on the battlefield gave basis to what I call necropolitics, especially about the killing of prisoners of war. Moreover, debates in the Athenian Assembly served to justify this kind of misbehavior, as shown in the Thucydidian account about the dispute between Cleon and Diodotus over the appropriate punishment of the revolting Mytelineans and the value of capital punishment.
Keywords: Thucydides; Peloponnesian War; Necropolitics